2019
DOI: 10.22158/selt.v7n2p163
|View full text |Cite
|
Sign up to set email alerts
|

Saudi EFL Learners’ Perceptions of the Benefits of ICT Integration into English Learning

Abstract: <p><em>This study focuses on exploring the benefits perceived by Saudi English as a Foreign Language (EFL) students of integrating Information and Communication Technology (ICT) into English learning and teaching. It also aims to determine their use of ICT and their attitudes to its use in learning and teaching. Data were collected through a questionnaire survey from 120 female preparatory year students studying at an English Language Institute (ELI) at a University in Saudi Arabia. The quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Participant 7 said that, "They are more interested." The responses of the participants are supported by Gamlo (2019) stated in literature review that integration of ICT provides a productive platform for the teachers and students to have a healthy environment for the process of teaching and learning. Therefore, ICT use becomes helpful for literature teachers because of its participatory benefits for the students as well.…”
Section: Enhanced Learner Interestmentioning
confidence: 68%
See 3 more Smart Citations
“…Participant 7 said that, "They are more interested." The responses of the participants are supported by Gamlo (2019) stated in literature review that integration of ICT provides a productive platform for the teachers and students to have a healthy environment for the process of teaching and learning. Therefore, ICT use becomes helpful for literature teachers because of its participatory benefits for the students as well.…”
Section: Enhanced Learner Interestmentioning
confidence: 68%
“…Additionally, the results also showed that the integration of ICT supported learners in the form of active participation, clarifying the concepts, innovation and interaction involved in learning English literature with ease leading to enhanced learner autonomy as discussed by (Gamlo, 2019). Therefore, the participants recommended the integration of ICT tools for keeping in view the supportive nature of ICT and digital access to educational material.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In research on foreign language learning, scientists have focused on the problems of mobile learning (Mlearning), e-learning (E-learning). Evidence of this is the emphasis on learning English as a foreign language using mobile devices -smartphones, tablets, mobile phones -in educational institutions in Taiwan [4], Thailand [5], Saudi Arabia [6], [7].…”
Section: Introductionmentioning
confidence: 99%